KONTRIBUSI HASIL BELAJAR SIKLUS AKUNTANSI DAN KKPI TERHADAP PENGOPERASIAN SOFTWARE MYOB ACCOUNTING - Imam Setiyono, ; Ika Nurmalasari, (Pendidikan Ekonomi, 2012)
The advancement of the information and technology has affected computer-based accounting information system. One of which is myob accounting. The study is aimed to know whether the learning result of accounting cycle and computer skill and information management to the operation of myob accounting software or not; also the research wanted to know to what extent the learning competence of accounting cycle and computer skill and information management contribute to myob accounting. The result of the study shows that calculation of F test was 11.874 with F table of 3.25. From the data analysis, its contribution is considered significant, which is 62%. Meanwhile, the individual contribution for learning result shown with calculation of t test was 3.297 with t table is 2.03. The learning result of computer skill and information management against software operation of myob accounting shown by the calculation of t test was 2.184 with t table 2.03. Thus, both hypotheses are proved.